2018
DOI: 10.1039/c7cc07344e
|View full text |Cite
|
Sign up to set email alerts
|

A far-red fluorescent probe based on a phospha-fluorescein scaffold for cytosolic calcium imaging

Abstract: The far-red emissive fluorescent probe CaPF-1 based on a phospha-fluorescein scaffold enables the detection of cytosolic calcium ions in living cells. The probe can be excited in the red region (λ = 636 nm) and exhibits a sufficiently high fluorescence turn-on response in the far-red region (λ = 663 nm) upon complexation with calcium ions. The hydrophilic and anionic characteristics of this phospha-fluorescein fluorophore allowed the cytosolic localization of CaPF-1. Moreover, it was possible to visualize hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…With respect to the predecessor 1 c , the performed changes of the molecular structure resulted in a remarkable 12 103 cm 1 (362 nm) bathochromic shift of fluorescence demonstrated by 6 c . It is important to note that the emission characteristics of 5 c and 6 c in organic solvents place them among the most efficient and red shifted organophosphorus dyes reported to date . The photoinduced intramolecular charge transfer leads in turn to large Stokes shifts of approximately 7600 cm −1 (280 nm, 5 c ) and 4700 cm −1 (230 nm, 6 c Figure ), minimizing the reabsorption, which is crucial for practical imaging applications…”
Section: Resultsmentioning
confidence: 66%
“…With respect to the predecessor 1 c , the performed changes of the molecular structure resulted in a remarkable 12 103 cm 1 (362 nm) bathochromic shift of fluorescence demonstrated by 6 c . It is important to note that the emission characteristics of 5 c and 6 c in organic solvents place them among the most efficient and red shifted organophosphorus dyes reported to date . The photoinduced intramolecular charge transfer leads in turn to large Stokes shifts of approximately 7600 cm −1 (280 nm, 5 c ) and 4700 cm −1 (230 nm, 6 c Figure ), minimizing the reabsorption, which is crucial for practical imaging applications…”
Section: Resultsmentioning
confidence: 66%
“…The reported λ abs , ε, λ em , ϕ FL , or p K a values closely resembled those of 25 . Very recently, Taki, Yamaguchi et al developed a proof‐of‐concept for a new fluorescent probe for bioimaging. They functionalized a phosphafluorescein derivative with a 1,2‐bis(2‐amino‐phenoxy)ethane‐ N , N , N′,N′ ‐tetraacetic acid (BAPTA) through a 2,6‐dimethoxyphenyl moiety (compound 27 , Figure ), which was utilized for the selective binding of Ca 2+ ions.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
“…We have previously reported that POFs and PORLs exhibit remarkable photostability, surpassing that of their oxygen‐ and silicon‐substituted counterparts . As for POR dyes, two groups have independently reported dyes that contain P(=O)Me and P(=O)OH or P(=O)OR moieties, and their utility as NIR‐emissive probes in fluorescence imaging.…”
Section: Figurementioning
confidence: 99%